Study of Etiology, Symptomatology of Uterine Prolapse and to Grade the Severity according to Pop-Quantification System - Mirza Wahab, Baig Zara Unisa; Tandale, Mahesh; Nagapurkar, Swati (Journal of Neonatal Surgery, 2025)
Background: Uterine prolapse, the descent of the uterus into or beyond the vaginal canal due to weakening of the pelvic floor muscles and ligaments, remains a significant health issue in women, particularly in developing countries. It often leads to distressing symptoms that impact quality of life and is commonly underreported due to sociocultural barriers. Objectives: To assess the clinical profile, risk factors, and severity of uterine prolapse in women attending the gynecology outpatient department (OPD) of a tertiary care hospital. Materials and Methods: This prospective clinical study was conducted over a defined period among patients presenting with symptoms of pelvic organ prolapse. Detailed histories were taken, and clinical examinations were performed using the Pelvic Organ Prolapse Quantification (POP-Q) system. Relevant demographic and clinical data were collected and analyzed statistically. Results: The majority of women affected were multiparous and above 40 years of age. Prolonged labor, home deliveries, and lack of postnatal care were common risk factors. Most patients presented in stage III or IV of uterine prolapse. Pelvic discomfort, mass per vagina, urinary complaints, and sexual dysfunction were the predominant symptoms. Surgical intervention was the preferred mode of treatment in advanced cases. Conclusion: Uterine prolapse is a common yet preventable condition. Awareness, early diagnosis, and accessible gynecological services can significantly reduce disease burden and improve quality of life for affected women. Community-based education and promotion of institutional deliveries are essential public health strategies to combat this issue